Comparison of future intensity duration frequency curve by considering the impact of climate change: case study for Kuching city - Kuok, Kelvin K.K; Mah, D.Y.S.; Imteaz, M.A; Kueh, S.M (Elsevier B.V., 2016)
Floods are occurring more frequently nowadays. The most common parameter used to analyse the flood severity is average recurrence interval (ARI). Very often, hydrologist found that the severity of flood is 100-year ARI. However, there is a possibility that the 100-year ARI flood severity will hit the same place again after a few months later. The two main possible reasons are (1) future warmer temperatures will increase future extreme precipitation extremes and (2) limited length recorded rainfall data had derived inaccurate Intensity duration frequency (IDF) curves. Therefore, there is an initiative in this study to derive future IDF curve by considering the future rainfall using ‘delta’ approach. The annual maximum precipitations for 2020s, 2050s and 2080s are generated using Statistical Downscaling Model (SDSM), neural network (NN) with scale conjugate gradient and Cuckoo search optimization algorithms. The selected study rainfall station is Kuching Airport. Results revealed that the newly projected IDF curves at various durations and ARIs are slightly higher than historical IDF curve. However, this research is still in the nascent stage and the results obtained are not finalized yet. More investigation works are carried out currently to establish reliable relationships between daily and sub-daily extreme precipitations based on the scaling general extreme value distribution.